Chronische Myeloische Leukämie - Hochhaus, Andreas; Eigendorff, Ekkehard; Ernst, Thomas (DMW - Deutsche Medizinische Wochenschrift, 2018)
The advent of tyrosine kinase inhibitors (TKI) has improved prognosis and outcome of patients with chronic myelogenous leukemia (CML) considerably. In comparison to imatinib, first line use of second generation inhibitors nilotinib, dasatinib and bosutinib lead to faster and deeper molecular remissions accompanied by a novel adverse event profile. Essential part of the management of CML patients is a consequent use of cytogenetic and molecular follow up with standardized methods to regularly assess the remission status. Long lasting remission without treatment in an important minority of patients prompted the hope for curability of CML. The use of interferon alpha in parallel with or after TKI therapy is associated with the induction of an immune response against the leukemic clone with further improved remission rate. The cooperative management of CML patients permits the early use of novel treatment options in patients at risk.
Keywords: Chronische myeloische Leukämie; Tyrosinkinase-Inhibitoren; BCR-ABL